2184. Surveillance System of Healthcare-Associated Infection in High and Upper-Middle Income Countries: A Scoping Review. (26th November 2018) - Takaya, Saho; Matsunaga, Nobuaki; Hayakawa, Kayoko; Moriyama, Yuki; Katanami, Yuichi; Tajima, Taichi; Tanaka, Chika; Kimura, Yuki; Saito, Sho; Kusama, Yoshiki; Morioka, Shinichiro; Fujitomo, Yumiko; et al.
Abstract: Background: Healthcare-associated infection (HCAI) is a major public health concern. HCAI surveillance is one of the five areas of focus of the Japanese action plan for antimicrobial resistance. In order to establish a Japanese HCAI surveillance system, we performed a scoping review about HCAI surveillance systems in the world. Methods: The search strategy consists of three Methods. academic literature review, Google search, and questionnaire to the Embassies of Japan in target countries. The target countries were 59 high and 79 upper-middle income countries defined by country income classification for the World Bank. The following information was reviewed: name of the system, official website, languages used in official website, foundation year, operating body, frequency, mode of participation, target population, types of target infections, types of target pathogens, definition of HCAI, and surveillance parameters. Online accessibility of the official websites was assessed through Google search. Results: Forty-one (29.7%) countries (34 [57.6%] high and 7 [8.8%] upper-middle income countries) are found to have national HCAI surveillance systems; 23 from Europe, 9 from Asia, 7 from Americas, and 2 from Oceania. Thirty-four (82.9%) countries have at least one official website, of which seven (20.6%) was identified in the top 30 hits through Google search in English. Surgical site infection (SSI) is the most surveyed infection (28 [68.3%] countries); catheter-related blood stream infection (CRBSI) in 25 (61.0%) countries, and catheter-associated urinary tract infection, ventilator-associated pneumonia, and Clostridium difficile infection (CDI) in 22 (53.7%) countries. MRSA is the most commonly surveyed pathogen (30 [73.2%] countries) followed by VRE in 22 (53.7%) countries. Most countries' systems follow or modify CDC/NHSN definition. European countries tend to have CDI surveillance and to have more selected surveillance targets than others. Conclusion: HCAI surveillance system is more in place in high income countries than in upper-middle income countries. Although surveillance targets vary between countries, SSI, CRBSI, and MRSA are surveyed in two thirds of the countries. Online accessibility of the official website is an area to be improved. Disclosures: All authors: No reported disclosures.